Compression Characteristics of Water Hyacinth Plant - Tiwari, Ghanshyam; Sharma, Ajay Kumar; Singh, Pratap (Journal of Agricultural Engineering, 2009)
Studies were carried out to observe the effect of compression pressure on compression characteristics of water hyacinth (Elchhorma crassipes) plant. There was rapid reduction in volume and weight and bulk density of the compressed plant during initial and later stages of compression process. Compression pressure of 2.63 MPa was required to get maximum volume (94 %) and weight (29.76 %) reduction of water hyacinth.